Khul' in Egypt Between Theory and Practice a Critical Analysis for Khul' Implementation - Samaha, Nivine (AUC Knowledge Fountain, 2017)
As a Prelude, Law is a social Phenomenon that reflects the culture of the society producing it and adapts to the Requirements of the environment in which it exists being a fundamental element of its structure and cultural character. However, this is not always the case in reality and in order to detect the level of accuracy of Schacht's comment and to what extent it walks in conformity with the mundane practicalities, this study is being presented to critically re-assess the "Khul'" Law implementation in Egypt throughout the last fifteen years since its first emanation in year 2000, by the advent of the Millennium, till nowadays, and to define the discrepancies between its theoretical perspective as a coded article in a Law and its actual application on the society itself